The Implementation Freedom of Education in Extracurricular at Mutiara Ilmu Pandaan Elementary School - Priyanto Widodo; Muslimatul Ilmiyah (JournEEL, 2019)
This study aims to find out: how the application of freedom in education in Mutiara Ilmu Elementary school,how the extracurricular election system is available at Mutiara Ilmu Elementary School. The data used are observation, interviews, and documentation. Datathatobtained in this study were analyzed using descriptive analysisqualitative with the stages of reducing data, and withdrawalconclusion.The results of the study show that: In extracurricular elections there is no coercion by the teacher towards students. students are given complete freedom in terms of extracurricular elections. even students are given the opportunity to carry out trials, if they feel comfortable, they can continue the extracurricular for one semester, if they feel uncomfortable they may move, but they only get one chance to move extracurricular